DNA Methylation-Driven Genes for Developing Survival Nomogram for Low-Grade Glioma - Guo, Yingyun; Li, Yuan; Li, Jiao; Tao, Weiping; Dong, Weiguo (Frontiers in Oncology, 2022)
Low-grade gliomas (LGG) is heterogeneous and current predictive models for LGG are either unsatisfactory or not user-friendly. The specific objective of this study was to establish a nomogram based on methylation-driven genes combined with clinicopathological parameters for predicting the prognosis of LGG. Differential expression, methylation correlation and survival analysis were performed in 516 LGG patients using RNA and methylation sequencing data with accompanying clinicopathological parameters from the Cancer Genome Atlas (TCGA). LASSO regression was further applied to select the optimal prognosis-related genes. The final prognostic nomogram was then built together with prognostic clinicopathological parameters. The predictive efficiency of the nomogram was internally validated in training and testing groups and externally validated in the Chinese Glioma Genome Atlas (CGGA) database. Three DNA methylation-driven genes, ARL9, CMYA5 and STEAP3 were identified as independent prognostic factors. Together with IDH1 mutation, age and sex, the final prognostic nomogram was built with the highest AUC of 0.930 and demonstrated stable consistency in both internal and external validation. The prognostic nomogram could predict personal survival probabilities for LGG patients and serve as a user-friendly tool for prognosis evaluation, optimizing the therapeutic regimes and management for LGG patients.